Strategic Planning Design in The Development of Multifunction Services of North Nias Public Library - Simanjuntak, Dilli Timoria (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
Strategic planning in library services is becoming needs today in responding to challenges in the era of industrial revolution 4.0. Strategic planning is also needs to respond the role of libraries as institution for providing information and knowledge in educating and empowering the nation. Thus, the strategic planning design is needed as a reference in developing future-oriented library services. This research aims to formulate the North Nias Public Library’s strategic planning design in improving public services. The research method was descriptive qualitative by collecting data through interview, observation, and documentation. The results of this study were North Nias Public Library’s strategic planning design with Hensley-Schoppmeyer Model which become a reference in developing the multifunctional services of North Nias Public Library in the future and the three pillars of strategic planning stages, i.e. consensus; cooperation; and proactive, creative, and contextual actions.